Pelanggaran Kode Etik Notaris Yang Bekerjasama Dengan Biro Jasa - Elsa Halida Saputri; Siti Hajati Hosein (Universitas Muhammadiyah Purwokerto, 2023)
difficulty getting clients, because people will tend to use the services of the same notary because of the client's sense of trust in the notary. Therefore, it is not uncommon for notaries to use intermediary services in the form of service bureaus to get clients. The research method used is centralized research with a normative juridical nature. The results of this study are notaries who violate the code of ethics in the form of collaborating with service bureaus whose sanctions in the Code of Ethics are in the form of reprimands, warnings, temporary dismissal from the association, and dishonorable discharge from the association. hesitate because of fellow notaries. Furthermore, the deed made with the intermediary of the service bureau will be relegated to a private deed due to the non-fulfillment of the elements of reading by a notary and subsequent signatures by the appearers, witnesses, and also notaries, and interest to the notary. Furthermore, it will be described in the introduction, subtitles, and closing.Keywords: notary, service bureau, deed degradation